Sleep apnea in people with Down syndrome: Causes and effects of physical activity? - Nguyen, Duy-Thai; Bricout, Véronique-Aurélie; Tran, Hong-Tram; Pham, Van-Hung; Duong-Quy, Sy (Frontiers in Neurology, 2023)
Poor sleep quality is recognized as a major risk factor for poor health, increasing the incidence of serious chronic diseases. In people with Down syndrome, sleep apnea prevalence is significantly greater, it is caused by genetic, anatomical, endocrine, and metabolic abnormalities. The consequences of sleep disruption due to sleep apnea are very serious, especially in terms of neurocognitive and cardiovascular effects, leading to reduced life expectancy and quality of life in this population. However, the management, care, and treatment of related disorders in people with Down syndrome are still inadequate and limited. Therefore, this article wants to increase understanding and awareness about sleep apnea and the benefits of physical activity in improving sleep quality in the Down syndrome community, families, and their care specialists.